Cathodic stripping voltammetry of 2,3-dichloroquinoxaline and 1,4-dichlorophthalazine reactive dyes and their hydrolysis products : reactive Red 41 and Reactive Red 96 - Mohd. Yusoff, A. Rahim; Fogg, Arnold G.; Ahmad, Rahmalan (Elsevier, 1998)
Preliminary studies of the feasibility of monitoring by cathodic stripping voltammetry the hydrolysis of two further types of reactive dyes have been made. The azo reduction peak in differential pulse cathodic stripping voltammograms of the 2,3-dichloroquinoxaline reactive dye, Reactive Red 41, and in those of its hydrolysis product are sufficiently separated for the hydrolysis of Reactive Red 41 to be followed using the heights of these peaks. In the case of the 1,4-dichlorophthalazine reactive dye, Reactive Red 96, the azo peaks of the reactive and hydrolysed dyes are too close to be used to monitor the hydrolysis reaction, but peaks associated with reduction of the 1,4-dichlorophthalazine group are present which could be used to monitor the hydrolysis of Reactive Red 96.